Practical technique for knowledge acquisition & dissemination in mobile environment - Wan Ishak, Wan Roslina; Abdullah, Rusli; Selamat, Mohd Hasan; Jaafar, Azmi; Wan Mayu Othman, Wan Noor Rafida (Universiti Utara Malaysia, 2008)
KM system (KMS) supports, creates, captures, stores and disseminates expertise and knowledge. The idea of mobile KMS is to ensure that the right information is delivered to the right person just in the right time using mobile devices. However, locally, we are not quite familiar with the term mobile KMS (mKM system) since it is still a new area that are still evolving. In this paper, we will share techniques that we are going to use in building our own mKM system with the hope that it can helps other organizations that wants to develop their own mKM system.